2016
DOI: 10.1002/ceat.201500660
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Fluidized‐Bed Catalyst Attrition Behavior

Abstract: Particle attrition is a prevalent problem in fluidized beds due to continuous moving of catalyst particles. It is always operated at high temperature either for lab-or industrial-scale fluidized beds. The influence of temperature on the attrition behavior of commercial methanol-to-olefins (MTO) and fluid catalytic cracking (FCC) catalysts is analyzed in a three-orifice lab-scale fluidized bed device from room temperature to 600°C. The two catalysts are found to be alike in attrition mode. Both change from a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
0
6
2
Order By: Relevance
“…Other factors which the study identified that could lead to attrition are the malfunction of trickle valves and overloading of the cyclones. In this study, however, Temperature was not found to play a significant role in the catalyst loss and attrition process; although the work of Hao et al (2016) reported that high temperatures could alter the attrition mechanism from abrasion to fragmentation. Hao et al (2016) equally highlighted the significance of temperature in the attrition process and such, the need to maintain the dense phase temperature as close to the design value as possible so as not to expose the catalyst to undue thermal stress.…”
Section: Technical Evaluationcontrasting
confidence: 55%
See 1 more Smart Citation
“…Other factors which the study identified that could lead to attrition are the malfunction of trickle valves and overloading of the cyclones. In this study, however, Temperature was not found to play a significant role in the catalyst loss and attrition process; although the work of Hao et al (2016) reported that high temperatures could alter the attrition mechanism from abrasion to fragmentation. Hao et al (2016) equally highlighted the significance of temperature in the attrition process and such, the need to maintain the dense phase temperature as close to the design value as possible so as not to expose the catalyst to undue thermal stress.…”
Section: Technical Evaluationcontrasting
confidence: 55%
“…Particle size has been studied as a factor of attrition using a jet-cup apparatus for several FCC catalysts (Wu et al, 2015), while Chen et al (2008) studied the attrition of catalyst particles in a high-velocity air-jet apparatus. Particle morphology, system composition, and operating conditions are other key factors reported to affect the attrition of catalyst particles (Hao et al, 2016;Fiske, 2013). Attrition modes range between abrasion and fragmentation resulting in the production of elutriate fines which do not alter the composition of the mother particle as well as particle breakage, respectively (Arrington et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For the industrial implementation of the DTO process, with a technology similar to that of the MTO process [22] (interconnected bubbling fluidized bed reactor and regenerator), the attrition problem of the HZSM-5 must be solved [23]. For this reason, zeolite is agglomerated within a matrix that provides the catalyst particles with the appropriate mechanical and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanically stressed component particles might break into small pieces during the storage, transportation, and handling. Particle breakage can significantly influence the mechanical behavior of granular assembly, 2,3 the flow of the interstitial fluid, 4,5 and the inter‐ and intraphase transfer performances 6,7 . Quantifications of the mechanical strength and the crushing probability of particles under various stress conditions are thus obviously useful to accurately predict and characterize the breakage behavior of particles inside granular assembly and also its possible influences.…”
Section: Introductionmentioning
confidence: 99%